Answer:
[tex]f(x)=x(x-1)(x^2-2x+2)[/tex]
Step-by-step explanation:
The standard polynomial is given by:
[tex]f(x)=a(x-p)(x-q)...[/tex]
Where a is the leading coefficient and p and q are the zeros.
We are given that the zeros are x = 0, 1, and 1 + i.
First, by the Complex Root Theorem, if 1 + i is a zero, then 1 - i must also be a zero.
Therefore:
[tex]f(x)=1(x-(0))(x-(1))(x-(1+i))(x-(1-i))[/tex]
Simplify:
[tex]f(x)=x(x-1)(x-(1+i))(x-(1-i))[/tex]
Expand the third and fourth factors:
[tex](x-(1+i))(x-(1-i))=(x-(1+i))(x)-(x-(1+i))(1-i)[/tex]
Distribute:
[tex]=x^2-x-ix-(x(1-i)-(1+i)(1-i))[/tex]
Expand:
[tex]=x^2-x-ix-x+ix+(1-i+i-i^2)[/tex]
Therefore:
[tex]=x^2-2x+(2)=x^2-2x+2[/tex]
Hence, our polynomial function is:
[tex]f(x)=x(x-1)(x^2-2x+2)[/tex]